ZINKIN ZBORNIK. Ur. Marko Jesenšek: Selnica ob Dravi: Občina, 2020. - Volmajer, Barbara; Volmajer, Metka; Vogrin, Oto (Slavia Centralis, 2020)
The authors of the article present the book Zinkin zbornik (Zinka’s collection of scientific papers), which was written in memory of academician Zinka Zorko as an honorary citizen of the municipality of Selnica ob Dravi.